Characteristics Properties of Autopsy Cases with Ethyl Alcohol and Evaluation of Their Causes of Death - Balcı, Yasemin; Göçeoğlu, Göçeoğlu; Çekiç, Edip Güvenç; Yürürdurmaz, Betül; Savran, Bülent (The Bulletin of Legal Medicine, 2021)
Introduction: Ethyl alcohol intoxication and abuse take place in the world and in Turkey as an important public health problem. In this study, the data of cases with ethyl alcohol as a result of toxicological examination in autopsies were compared. The aim of this study was to determine the characteristics of autopsy cases with ethyl alcohol and to compare the causes of death. Method: The results of all autopsies performed by “Muğla Forensic Medicine Institution” between 2013-2018 were evaluated retrospectively. When the alcohol detection rates were analyzed by years, it was shown that 42.2% of the autopsies performed in 2013 were found to be alcohol, while autopsies performed in 2018 were found to be 17.2% (P = 0.000). Alcohol was found in 15.8% of the autopsies performed in women and 28.8% in men (P = 0.000). The cause of death in 25.9% of the cases with alcohol was defined as a self-existing disease (heart, lung, brain, liver, stomach, etc.), whereas this rate was 34.6% in cases without alcohol. The causes of death due to penetrating traumas (firearms, stab wounds) were 13.9% in alcohol-detected cases and 9.1% in alcohol-free cases. Discussion and Conclusion: It has been suggested that the differences in alcohol detection rates in autopsy cases may be related to awareness studies aimed at raising social awareness. It was suggested that the difference between alcohol detection and causes of death in autopsy cases could be related to alcohol use and increased frequency of depression / suicide risk.